Phyllode an Uncommon Tumor of the Breast - A Case Report - Prashanth K,; Veena P, (International Journal of Ayurveda and Pharma Research, 2022)
‘Phyllodes’ is a Greek word which means leaf- like. Phyllodes tumour, though appears well circumscribed, is characterized by irregular surface surface projections. These projections may be cut during surgical excision and predispose to recurrence. Phyllodes tumour shows a wide spectrum of activity varying from an almost benign condition to a locally aggressive, and sometime metastatic tumour. We report a 61 year old female patient presented with a lump on the  left breast. Excision was done and histo pathology report revealed phyllode tumour.